ON THE 70TH ANNIVERSARY OF KHIZRI AMIRKHANOVICH AMIRKHANOV - Tajmazov, Artur Israpilovic (History, Archeology and Ethnography of the Caucasus, 2019)
In December 2019 is the 70th anniversary of doctor of historical Sciences, Professor, academician of the Russian Academy of Sciences, head of the Department of stone age archaeology Institute of archaeology Russian Academy of Sciences, scientific head of the Institute of history, archaeology and Ethnography of the Dagestan Federal research center Russian Academy of Sciences, editor-in-chief of the journal "History, archaeology and Ethnography of the Caucasus" Khizri Amirkhanovich Amirkhanov.
Keywords: Khizri Amirkhanovich Amirkhanov; ANNIVERSARY; Full member of the Russian Academy of Sciences; editor-in-chief; History; Archaeology and Ethnography of the Caucasus